2006
DOI: 10.1677/erc.1.01239
|View full text |Cite
|
Sign up to set email alerts
|

Human melanoma cells express functional receptors for thyroid-stimulating hormone

Abstract: We have reported a high prevalence of hypothyroidism in the cutaneous melanoma population, suggesting that the pathologic hormonal environment of hypothyroidism promotes melanoma growth. The objective of this study was to test the hypothesis that TSH, which circulates at elevated levels in hypothyroid individuals, stimulates the growth of melanoma cells. Our results show that TSH receptors (TSHR) are expressed by virtually all cutaneous melanocytic lesions, including benign nevi, dysplastic nevi, and melanomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 20 publications
6
47
0
Order By: Relevance
“…According to Ellerhost et al results, TSH receptors are expressed by almost all cutaneous melanocytic lesions, including benign nevi, dysplastic nevi, and melanomas. In addition, higher expression is observed in malignant and pre-malignant lesions (12). We report here a newly identified cause of false-positive diagnostic WBS findings with low Tg level: Fistula tract accompanying the SG.…”
Section: Case Reportmentioning
confidence: 76%
“…According to Ellerhost et al results, TSH receptors are expressed by almost all cutaneous melanocytic lesions, including benign nevi, dysplastic nevi, and melanomas. In addition, higher expression is observed in malignant and pre-malignant lesions (12). We report here a newly identified cause of false-positive diagnostic WBS findings with low Tg level: Fistula tract accompanying the SG.…”
Section: Case Reportmentioning
confidence: 76%
“…Continuous monitoring of the thyroid function in melanoma patients is required because hypothyroidism can worsen due to malignant melanoma and this probably is associated with thyroid carcinoma, like in our case 2,5 .…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have reported that TSH is more likely to be expressed by dysplastic nevi than by benign nevi, and the dysplastic nevi of melanoma patients have a higher TSH expression than that of healthy individuals. Thus, TSH has been implicated in the malignant transformation of melanocytes to melanoma, and TSH stimulates the growth of melanoma cells 5,6 . On the other hand, the possibility has been suggested that the melanoma induces the thyroid dysfunction and this leads to hypothyroidism under the condition of low circulating thyroid hormone levels and concomitantly elevated TSH levels, although an autoimmune mechanism has also been suggested 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is very well known that stimulation of TSHR by TSH results eventually in production of THs, T 3 and T 4 in thyroid cells (Toccafondi et al 1982, Szkudlinski et al 2002. However, we also know that TSHR can be expressed by extrathyroidal tissues or cells (Haraguchi et al 1996, Hoermann 1996, Dutton et al 1997, Bell et al 2000, Agretti et al 2002, Tsai et al 2004, Ellerhorst et al 2006. For example, kidney cells were shown to express a functional TSHR that transmitted signals through cAMP (Sellitti et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the TSHR via TSH on thyroid cells leads to production of the thyroid hormones (THs), tri-iodothyronine (T 3 ) and thyroxine (T 4 ) (Toccafondi et al 1982). The TSHR expression by other tissue cells has also been reported (Haraguchi et al 1996, Hoermann 1996, Dutton et al 1997, Bell et al 2000, Agretti et al 2002, Tsai et al 2004, Ellerhorst et al 2006. However, exact function of its expression in extrathyroidal tissues has not been clarified.…”
Section: Introductionmentioning
confidence: 99%